2022
DOI: 10.37923/phle.2022.20.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Saphenous Vein Reflux and Treatment Plan

Abstract: Varicose vein is a prevalent disease and a cause of substantial morbidity. Venous reflux often originates from saphenous trunks and their tributaries. The great saphenous vein and small saphenous vein have major anatomical variations due to their embryological origin. Understanding of anatomic variation and reflux pattern is important to decide the target lesions for treatment and treatment modalities for symptom relief effectively and to prevent the future complications and recurrence. In this review, we purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…They also noted that there are limited data on the treatment effect of edema when only below-knee great saphenous vein (GSV) reflux or segmental reflux is present (7). Treatment for segmental reflux is generally unnecessary, even in the absence of edema (8). There seems to be a difference in perspectives regarding clinical class C3.…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that there are limited data on the treatment effect of edema when only below-knee great saphenous vein (GSV) reflux or segmental reflux is present (7). Treatment for segmental reflux is generally unnecessary, even in the absence of edema (8). There seems to be a difference in perspectives regarding clinical class C3.…”
Section: Discussionmentioning
confidence: 99%
“…To implement the CHIVA strategy, hierarchy of venous flow in the leg must be assessed using Doppler ultrasonography. Various patterns of saphenous reflux have been previously described; (5,6) these patterns are useful for guiding saphenous ablation therapy. In the CHIVA strategy, Teupitz shunt classification is used to categorize flow patterns in saphenous veins (7).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of non-saphenous vein reflux is not well-established, but emerging evidence suggests that it may be more common than previously thought. Studies have shown that non-saphenous vein reflux may be present in up to 9∼35% of patients with chronic venous insufficiency, indicating that it is a significant and under-recognized problem (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%